Approaches to evaluate nutrition of minerals in food - Xuan Wang; Yifan He; Qian Gao; Dong Yang; Jianfen Liang (Food Science and Human Wellness)
Numerous techniques have been developed to determine the bioavailability of minerals. Each method has specific detection objects with certain procedures to assure the results. This review focuses on a comprehensive comparison of the applications, advantages, and critical control points of these techniques. The commonly used approaches for assessing mineral bioavailability can be divided into three categories - chemical methods, in vitro models and in vivo tests. Chemical methods are first developed, and mainly simulating the digestion environment to give a rough prediction of mineral bioavailability. In vitro models mainly used different cells to simulate the process and environment of food digestion to assess the availability of minerals. In vivo tests are employing complex models to observe the bioavailability of minerals after complicated digestive process in animal models or human volunteers. This review summarizes the critical points of establishment of these relevant models, compares the advantages and limitations among three categories. Although no single bioavailability method is ideal for all micronutrients, certain methods under proper operation can indeed be employed to minimize the differences between simulated results and reality for effective evaluation of the bioavailability of minerals.